Tropomyosin is a minor but distinct allergen in patients with shrimp allergies in Japan. Issue 3 (17th June 2018) - Tsedendorj, Onon; Chinuki, Yuko; Ueda, Kiyoe; Kohno, Kunie; Adachi, Atsuko; Morita, Eishin
Abstract: Recently, purified allergens have been utilized for allergen‐specific IgE tests, which are highly useful because of their excellent specificity and sensitivity in identifying allergic patients. The purpose of this study was to evaluate the specificity and sensitivity of tropomyosin‐specific IgE test in the diagnosis of shrimp allergies in Japan. We enrolled 27 patients with shrimp allergy and five patients with atopic dermatitis, who had no history of allergic reactions to shrimp but showed positive results in tropomyosin‐specific IgE test, in this study. Tropomyosin‐specific IgE was determined by IgE immunoblotting and tropomyosin‐specific IgE test. Involvement of carbohydrate moieties in IgE binding to the allergens was examined by periodate treatment. Tropomyosin‐specific IgE was detected in 13 and positive in 10 of the 27 patients with shrimp allergy, whereas shrimp‐specific IgE was detected in 21 and positive in 20 of these 27 patients. Of the 13 patients with detectable levels of tropomyosin‐specific IgE, seven were confirmed to have tropomyosin‐specific IgE by immunoblotting analysis, whereas no IgE binding was seen in the five patients with atopic dermatitis, indicating the high specificity of the tropomyosin‐specific IgE test. The level of tropomyosin‐specific IgE was well correlated with those of shrimp‐specific IgE and Der p 10‐specific IgE. Our findings indicated tropomyosin is a minor but distinct allergen in patients with shrimp allergy, especially causing symptoms of OAS. Abstract : Recently, purified allergens have been utilized in allergen‐specific IgE tests, which are highly useful because of their excellent specificity and sensitivity in identifying allergic patients. The purpose of this study was to evaluate the specificity and sensitivity of tropomyosin‐specific IgE test in the diagnosis of shrimp allergies in Japan.